2012
DOI: 10.1016/j.bbadis.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of cerebral white matter integrity in cognitive aging

Abstract: In this article we review recent research on diffusion tensor imaging (DTI) of white matter (WM) integrity and the implications for age-related differences in cognition. Neurobiological mechanisms defined from DTI analyses suggest that a primary dimension of age-related decline in WM is a decline in the structural integrity of myelin, particularly in brain regions that myelinate later developmentally. Research integrating behavioral measures with DTI indicates that WM integrity supports the communication among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
347
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(411 citation statements)
references
References 202 publications
53
347
2
1
Order By: Relevance
“…In contrast, cortical thickness of older meditators was comparable to that of younger meditators. In a study on differences in fractional anisotropy (FA), an index of white matter integrity (Madden et al 2012;Madden et al 2009), Luders et al (2011) reported that the agerelated FA decrease was less pronounced in meditators than in controls. These cross-sectional studies provide a first indication that MM might protect against cognitive decline.…”
Section: Meditation Ageing and Cognitive Functionsmentioning
confidence: 99%
“…In contrast, cortical thickness of older meditators was comparable to that of younger meditators. In a study on differences in fractional anisotropy (FA), an index of white matter integrity (Madden et al 2012;Madden et al 2009), Luders et al (2011) reported that the agerelated FA decrease was less pronounced in meditators than in controls. These cross-sectional studies provide a first indication that MM might protect against cognitive decline.…”
Section: Meditation Ageing and Cognitive Functionsmentioning
confidence: 99%
“…FA and cognitive function relationships have been studied mainly in adults and older children (3,33), and some studies find lower RD in association with better cognition as an index of myelination (4,5). However, few studies have reported relationships between AD and cognition (1).…”
Section: Discussionmentioning
confidence: 99%
“…While low AD in the mouse model described above (Song et al, 2002) was associated with axonal injury, AD correlated positively with IIV. Studies have shown AD increases in normal aging and Alzheimer's disease (Agosta et al, 2011;Madden et al, 2011). Positive relationships between AD and IIV explain why FA was less strongly related to IIV than MD or RD.…”
Section: Effects Of Cognitive Demandmentioning
confidence: 99%